Customs Evasion and its Impact on Palestinian Customs Revenues - Assad Kamel Mustafa Musa (My University, 2005)
Customs evasion is one of the problems and obstacles precluding the government’s performance of its job: securing welfare and providing basic services to its citizens. To these two end, governments largely depend on customs given their significant contribution to the treasury coffers with the badly needed funds. Customs proceeds are considered one major resource for the treasury which governments cannot survive without. Customs evasion, in the Palestinian Territories, is one of the important factors behind the severe shortage which the Palestinian treasury suffers from. Customs revenues mainly come from trade with or through the Israeli side. It was found that 77% of Palestinian total foreign trade was with Israel. This high percentage is due to the extraordinary circumstances in the region. The difficult political conditions have made Palestinian foreign trade different from those of other countries. Palestinian economy and people are held hostage to the Israeli military occupation measures on the ground: prolonged closures, roadblocks, curfews, restriction on travel and control of border crossings. All these measures combined have led to an increase in customs evasion. In addition, the customs laws, effective in the Palestinian Territories, have some gaps or shortcomings and as a result, customs payers evade paying customs duties. The unfair economic agreements signed between Palestine Liberation Organization (PLO) and Israel have also had their heavy toll on the Palestinian treasury. This study aimed at identifying the Palestinian National Authority’s revenues, percentage of customs’ contribution to the public budget, sources of public revenues. By learning about the nature of the Palestinian customs and its evasion, in terms of organization, specializations and procedures, the researcher sought to examine the customs evasion phenomenon in terms of its types, pillars and penalties applied on customs evaders. This was in addition to the reasons behind customs evasion. The researcher also examined the international economic agreements, including GATT and Paris Economic Protocols (between the PNA and Israel), to find out their impact on customs revenues. He also focused, in his study, on how to check on the customs evasion phenomenon. To these ends, he depended on references, sources, documents and other primary materials such as the texts of the agreements signed between the PLO and other countries. In addition, the researcher managed to have access to directives, and guidelines issued by he Ministry of Finance. After data collection and analysis, it was found that the economic reasons played an important and effective role in increasing customs evasion. In addition, it was found that a number of moral, social and political factors were responsible for the rise in customs evasion cases. Further, the penalties, enforced by the Palestinian National Authority, played a leading role in increasing customs evasion. Besides, the laws enforced played a significant and effective role in increasing this phenomenon. Also the absence of a modern and updated Palestinian Customs Law is contributing to the spread of evasion from paying customs. To check on customs evasion, in the Palestinian Territories, the researcher recommends the following: 1. Enacting a new Palestinian customs law. 2. Training customs cadres to check on the customs evasion. 3. Setting up customs courts, in the Palestinian Territories, to settle customs disputes. This is in addition to developing the customs judicial apparatus. 4. Enhancing the role of both internal and external control of offices’ performance and evaluating/ assessing their effectiveness. 5. Toughening penalties on customs evaders. 6. Reformulating and renegotiating the agreements, including Paris Economic Protocols, signed by the PLO and Israel.

تعتبر ظاهره التهرب الجمركي من المشاكل والعقبات التي تحول دون أداء الدولة لمهامها التي تهدف إلى تحقيق الرفاهية وتقديم الخدمات الأساسية للمواطنين وذلك في، دول العالم، لما للجمارك من تأثير كبير في إمداد الخزانة العامة للسلطة بالأموال اللازمة لذلك، اذ تعتبر من الموارد الرئيسية للخزانة العامة بالأموال، بالاضافه إلى غيرها من الموارد الأخرى، ولعلنا لا نبالغ إذا اعتبرنا ظاهرة التهرب الجمركي واحدة من أهم الأسباب التي تؤدي إلى النقص المطرد في الخزانة الفلسطينية، المتمثلة بين الجانب الفلسطيني والإسرائيلي اذ تشكل التجارة مع الجانب الإسرائيلي وحدة أكثر من 77% من إجمالي التجارة الخارجية الفلسطينية، ولا شك ان هذه النسبة ننصف بظروف غير طبيعية تختلف عن بقية دول العالم متمثلة في ظروف سياسية صعبة، تتمثل في الاحتلال المتواصلة من إغلاق وحصار للمناطق الفلسطينية، وغيرها من الأسباب التي أدت إلى ظاهره التهرب الجمركي التي لها دور فعال بتأثير على الخزانة الفلسطينية، هذا بالإضافة إلى دور التشريعات الجمركية المطبقة بما فيها من ثغرات تدفع المكلف إلى التهرب الجمركي، إضافة إلى الاتفاقيات المبرمة ما بين منظمه التحرير وإسرائيل. إن الهدف من هذه الدراسة التعرف على إيرادات السلطة الفلسطينية ونسبه الجمارك من الموازنة العامة، ومصادر الإيرادات العامة، وللتعرف إلى الجمارك الفلسطينية والتهرب الجمركي من حيث تنظيمها، واختصاصاتها، والإجراءات الجمركية، يسعى الباحث إلى الوقوف إلى ظاهرة التهرب الجمركي وأنواعه، وأركانه والجزاءات المترتبة على التهرب الجمركي، وأسبابه، والحديث عن الاتفاقيات الدولية، اتفاقيه الجات واتفاقيه باريس الاقتصادية وأثرهما على الإيرادات الجمركية، وكيفيه الحد من ظاهره التهرب الجمركي. قام الباحث بجمع المعلومات اللازمة لذلك من، المراجع، والوثائق والاتفاقات المبرمة بين منظمه التحرير الفلسطينية والدول الأخرى، إضافة للتعليمات والمناشير الخاصة بوزارة المالية. وتوصلت هذه الدراسة إلى النتائج التالية: 1. تشكل الإيرادات الجمركية جزءاً كبيراً من الإيرادات العامة للسلطة الفلسطينية، وبما ان معظم المستوردات الفلسطينية هي سلع استهلاكية، يتم استيرادها عن طريق تجار إسرائيليين، فان الإيرادات الجمركية المحصلة على هذه المستوردات تعود للخزينة الإسرائيلية، تؤدي إلى خسارة مالية كبيرة للسلطة الفلسطينية. 2. غياب سيطرة السلطة الفلسطينية على المعابر الدولية الخارجية والداخلية، أدى إلى الاعتماد الكبير على إسرائيل في مجال التجارة الخارجية، اثر ذلك على الإيرادات الجمركية. 3. تراجع الإيرادات الجمركية والضريبة الفلسطينية بسبب الحصار الإسرائيلي للمناطق الفلسطينية. 4. غياب التشريعات الجمركية اللازمة والمحاكم المتخصصة. 5. وفرت اتفاقية باريس اطاراً مرجعياً وتنظيمياً لوزارة المالية في استخدام أدوات السياسة المالية، لكنها قيدت ضرائب القيمة المضافة، والضرائب الجمركية من خلال ربطهما بمستوياتها المعتمدة في الاقتصاد الإسرائيلي، مما اثر ذلك على التسرب المالي لصالح الخزينة الإسرائيلية. وتوصل الباحث إلى عدد من الوصيات أهمها: 6. الاهتمام بالإصلاح القانوني الشامل وتسريع تحضير قانون الجمارك الفلسطيني، والبدء في تفعيل المحاكم الجمركية الفلسطينية، وإيقاع عقوبات جدية للمتهربين. 7. إعادة تصميم الفاتورة الموحدة "المقاصة" بحيث تظهر بوضوح المنشأ الأصلي للبضاعة المشتراة من تجار إسرائيليين حتى تتمكن السلطة من المطالبة بالإيرادات الجمركية على هذه البضاعة. 8. استخدام وسائل الإعلام لزيادة وعي المواطنين بأهمية الإيرادات الجمركية في دعم الاقتصاد الفلسطيني. 9. الإسراع في الإشراف الكامل على المعابر، ونقل الصلاحيات في الضفة الغربية إلى السلطة الفلسطينية لتمكينها من تنفيذ الخطط الجمركية.
التهرب الجمركي وأثره في الإيرادات الجمركية الفلسطينية